CFD analysis of the main operating parameters for a complete braking friction system under transient working conditions - F. Orlandi; C. De Marco; S. Meleti; A. Manian; M. Milani; L. Montorsi (International Journal of Thermofluids)
A braking system represents a very complex physical system to be properly modelled since it involves the solution of multiphase flow and thermal distribution and multi-body motions under dynamic operating conditions. Most approaches focus on a single braking element coupling, generally between a steel and a friction material element, which demonstrated to be insufficient to predict the effective behaviour of these systems. The present work extends the approach adopted for a single braking couple, to include a full braking system including the disks and braking piston motions and the thermal dissipated energy along the braking event. The comprehensive numerical model allows to deeply analyse the thermal dissipation of the solid elements and the oil of the systems and thus the cooling efficiency of the lubricant oil can be calculated. Furthermore, a sensitivity analysis with respect of the main braking system operating parameters is carried out to investigate the influence of heat dissipation rate of the oil and the cooling efficiency of the full braking system. In particular, the lubricant oil flow rate, the thermal energy to be dissipated and the characteristic braking time are analysed. The most critical operating conditions are highlighted as well as the optimal configuration is defined.